Effect of multiparity on bone mineral density, evaluated with bone turnover markers - Terzi,Hasan (2017)
Abstract Objective: Our aim was to investigate the effect of parity on osteoporosis by evaluating bone mineral density, markers of bone turn-over and other factors that are effective in osteoporosis in multiparous (five deliveries or more) and nulliparous women in the post-menopausal period. Methods: A total of 91 multiparous (five deliveries or more) and 31 nulliparous postmenopausal women were included in this study. All patients were interviewed on sociodemographic characteristics, gynecologic history, personal habits, levels of physical activity, and life-long intake of calcium. Bone mineral density was measured at lumbar (L1-4) and femoral neck regions with Dexa. Results: The mean age of multiparous women was 58.79 ± 7.85 years, and the mean age of nulliparous women was 55.84 ± 7.51. The femoral BMD was 0.94 ± 0.16 and lumbar BMD 1.01 ± 0.16 in multiparous women, femoral BMD was 0.99 ± 0.16 and lumbar BMD 1.07 ± 0.14 in nulliparous women. There were no statistical differences between the femoral and lumbar T scores and BMD values of the two groups. Lumbar T scores and lumbar BMD showed a decrease with increasing total duration of breast-feeding in multiparous women. The independent risk factors for osteoporosis in the regression analysis of multiparous women were found to be the duration of menopause and body weight of 65 kg and less. Conclusion: There is no difference between the bone mineral densities of multiparous and nulliparous women. Females with lower body-weight and longer duration of menopause should be followed-up more carefully for development of osteoporosis.